Analisa Perilaku Gaya Hidup dan Body Image Remaja Putri di SMK Negeri 3 Kota Malang - Halim Kurrotu A’yun; Desiana Merawati (Jurnal Ilmu Psikologi dan Kesehatan | E-ISSN : 3063-1467, 2026)
Adolescence is a developmental stage characterized by physical, psychological, and social changes that may influence body perception. The influence of social media, sedentary lifestyles, unhealthy eating habits, and current beauty standards has caused many female adolescents to experience body dissatisfaction. This study aimed to analyze lifestyle behavior and body image among female adolescents at SMK Negeri 3 Kota Malang. The study used a quantitative descriptive method with a cross-sectional approach. The sample consisted of 91 female students from grades X and XI selected using cluster sampling and proportional random sampling techniques. Data were collected through questionnaires regarding physical activity, eating habits, social media use, and body satisfaction, along with anthropometric measurements including height, weight, and body mass index (BMI). The results showed that most students had low physical activity levels, high smartphone usage duration, and unhealthy dietary habits such as consuming fast food, sugary drinks, and high-fat snacks. Most respondents also experienced dissatisfaction with their body shape, particularly because they felt overweight, not tall enough, or inconsistent with current beauty standards influenced by social media and public figures. Low physical activity, unhealthy eating behavior, and high exposure to social media were associated with increased body dissatisfaction among female adolescents. Therefore, education regarding healthy lifestyles, regular physical activity, wise social media use, and self-confidence improvement is needed to promote positive body image among adolescents.